Numerical Methodology to Reduce the Drag and Control Flow around a Cam-Shaped Cylinder Integrated with Backward Splitter Plate - Sunil Chamoli; Amit Joshi; Sumit Rana; Suvanjan Bhattacharaya; Ashutosh Gupta; Siddharth Ghansela; Chinaruk Thianpong; Smith Eiamsa-ard (My University, 2023)
After publishing a research article in the year 2019, a cam-shaped cylinder was introduced, and the results expressed its ability to prevent the vortex from shedding. This makes the cam-shaped cylinder a better performer than the circular cylinder. This work is an extension of past work with the aim of further reducing drag by attaching a backward splitter plate to a cam-shaped cylinder. In an attempt to decrease drag and regulate the wake regime more efficiently than the traditional splitter plate control devices, a splitter plate flow departure control device is presented in this paper for a low Reynolds number flow range (Re = 50–200). It has been noted that when plate length increases, integral parameters like drag, lift, and Strouhal number do not change monotonically. The Strouhal number (St) increases with a drop in D2/Deq, but the average drag reduces with a rise in Re and a decrease in D2/Deq, respectively. In terms of decreased drag, the current cam-shaped cylinders attached to a rearward splitter plate have shown their superiority to other bluff bodies.
Keywords: Strouhal number; Splitter plate; Vortex shedding; Flow Control; Splitter; Krmn vortex street; Fluid Dynamics and Vibration Analysis